Optimal solar radiation sensor network design using spatial and geostatistical analyses. Issue 1 (2nd January 2016) - Teegavarapu, Ramesh S.V.; Pathak, Chandra S.; Mecikalski, John R.; Srikishen, Jayanthi
Abstract : A methodology for optimal ground-based sensor network design for an evapotranspiration (ET) estimation method which uses solar radiation as the only parameter is developed and evaluated in this study. The methodology employs geospatial analyses and a geostatistical approach, and data from ground-based sensors and satellite-based estimates of solar insolation (i.e. total amount of solar radiation energy received on a given surface area during a given time) considering the spatial variability of the data. The applicability of the methodology is demonstrated by using Geostationary Operational Environmental Satellite (GOES)-estimated and 29 ground sensor-based observed solar insolation data in the South Florida region of the USA. Results indicate that the optimal design of network depends on the spatial variability of insolation, analysis block size defined based on region-specific radiation characteristics, and the standard error used as a metric of network estimation accuracy.